DETERMINANTS OF DEMAND FOR FRESH VEGETABLES IN THE SLOVAK REPUBLIC - Elena Hoskova; Iveta Zentková (Ekonomika Poljoprivrede (1979))
Vegetables are among the most important foods because of the health benefits of eating them. The main objective of this paper is to investigate the effect of income, own price and price of other vegetables on the demand for vegetables in the Slovak Republic. Descriptive statistics and regression analysis are used for the analysis. The data are drawn from the Statistical Office of the Slovak Statistical Office (2001 2019). The results of the analyses indicated that demand for lettuce (EID=3.48) and peas (EID=-4.82) responded most strongly to the change in income. The demand response to a change in the price of other vegetables was stronger than the response to a change in own price. Demand for cauliflower, and lettuce responded most strongly to the change in price of other vegetables. To increase vegetable consumption, we recommend reducing the price of complements or increasing the price of substitutes.